2006
DOI: 10.1123/jpah.3.s1.s118
|View full text |Cite
|
Sign up to set email alerts
|

Community Design and Access to Recreational Facilities as Correlates of Adolescent Physical Activity and Body-Mass Index

Abstract: There was limited evidence that both community design and access to recreation facilities variables were associated with adolescent physical activity, but additional built environment variables need to be studied that have particular relevance for youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
206
6
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(226 citation statements)
references
References 28 publications
(18 reference statements)
6
206
6
2
Order By: Relevance
“…Studies conducted in the USA and Australia [14][15][16] are inconclusive with regard to the association between adolescents' physical activity and residential density. Our findings suggest there may be a negative association between population density and recreational physical activity for adolescents, in a rapidly expanding urban area of China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in the USA and Australia [14][15][16] are inconclusive with regard to the association between adolescents' physical activity and residential density. Our findings suggest there may be a negative association between population density and recreational physical activity for adolescents, in a rapidly expanding urban area of China.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another study in the USA reported that no link between residential density and accelerometer-measured physical activity among 11-15 year olds. 16 Although the quantity of relevant literature is modest, these differing associations for two Western countries suggest associations between residential density and physical activity may vary in different contexts, reinforcing the need to understand how aspects of urban form are associated with adolescents' recreational physical activity in the rapidly urbanizing context of Mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…Third, most studies examined subcomponents of physical activity, such as transportation or recreation activities, but the contribution of built environments to total physical activity, that should be most strongly related to health outcomes, has seldom been reported. [11][12][13] Finally, because studies have been conducted within single countries, limited environmental variability may lead to underestimation of true associations with physical activity. Underestimated associations could reduce the apparent relevance of built environment changes as physical activity promotion strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have quantified access to facilities in terms of respondents_ self-reported perceptions [1][2][3] while others have calculated objective measures [4][5][6] like the number of facilities within a defined radius or the distance to the nearest facility using geographic information systems (GIS). What is not understood is whether there is a close relationship between the number and proximity of objectively measured neighborhood physical activity facilities and youths_ perceptions of access to these resources.…”
Section: Introductionmentioning
confidence: 99%